2015
DOI: 10.1007/s10142-015-0450-3
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis of SAUR gene family in citrus and its transcriptional correlation with fruitlet drop from abscission zone A

Abstract: Small auxin-up RNA (SAUR) gene family is large, and the members of which can be rapidly induced by auxin and encode highly unstable mRNAs. SAUR genes are involved in various developmental and physiological processes, such as leaf senescence, fruitlet abscission, and hypocotyl development. However, their modes of action in citrus remain unknown. Hereby, a systematic analysis of SAUR gene family in citrus was conducted through a genome-wide search. In this study, a total of 70 SAUR genes, referred to as CitSAURs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…Only one SAUR gene in Arabidopsis has an intron, while none of the OsSAURs in rice harbors any intron. Among other species, 6 out of 58 SAUR genes in maize, 3 out of 99 SAUR genes in tomato, 9 out of SAUR genes in potato, 10 out of 70 SAUR genes in citrus contained introns based on the sequenced genomes [ 3 , 6 , 8 10 ]. Similar phenomenon in cotton was found in this study in that about 9.3% of the SAUR genes in cotton carried introns.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only one SAUR gene in Arabidopsis has an intron, while none of the OsSAURs in rice harbors any intron. Among other species, 6 out of 58 SAUR genes in maize, 3 out of 99 SAUR genes in tomato, 9 out of SAUR genes in potato, 10 out of 70 SAUR genes in citrus contained introns based on the sequenced genomes [ 3 , 6 , 8 10 ]. Similar phenomenon in cotton was found in this study in that about 9.3% of the SAUR genes in cotton carried introns.…”
Section: Discussionmentioning
confidence: 99%
“…Since the first SAUR gene was identified in elongating soybean hypocotyl sections [ 5 ], members of this gene family have been identified by genome-wide analyses in diverse plant species, such as Arabidopsis [ 3 ], rice [ 6 ], sorghum [ 7 ], tomato [ 8 ], potato [ 8 ], maize [ 9 ], citrus [ 10 ], and ramie [ 11 ]. In total, more than 674 SAUR genes were identified from different species, but only a small portion of them have been functionally characterized.…”
Section: Introductionmentioning
confidence: 99%
“…SAUR family genes ( SAUR22, 23 and 32 ) were up-regulated in weeping willow. Chen et al revealed that SAUR19-24 function as positive effectors of cell expansion [ 35 ], and Xie et al demonstrated that SAUR32 induces short, hookless hypocotyls when overexpressed in Arabidopsis [ 36 ]. In addition, most GH3 family genes were up-regulated in weeping willow.…”
Section: Discussionmentioning
confidence: 99%
“…The SAUR gene family contains numerous auxin-response genes in different species, including 81 SAURs (with 2 pseudogenes) in Arabidopsis (Hagen and Guilfoyle 2002), 58 SAURs (with 2 pseudogenes) in rice (Jain et al 2006), 18 SAURs in moss (Rensing et al 2008), 71 SAURs in sorghum (Wang et al 2010), 134 SAURs in potato, 99 SAURs in tomato (Wu et al 2012), 79 SAURs in maize (Chen et al 2014) and 70 SAURs in citrus (Xie et al 2015). These reports also reported their main functions in these species.…”
mentioning
confidence: 97%
“…One of the vital auxin-responsive families is the small auxin-up RNA (SAUR) gene family. SAUR genes have been identified in mung bean (Yamamoto et al 1992), pea (Guilfoyle et al 1993), tomato (Zurek et al 1994), Arabidopsis (Gil et al 1994), apple (Watillon et al 1998), radish (Ann et al 1998), maize (Yang and Poovaiah 2000), rice (Jain et al 2006b), moss (Rensing et al 2008), sorghum (Wang et al 2010), potato, tobacco, pepper, petunia (Wu et al 2012), cotton (Yang et al 2012), litchi (Kuang et al 2012), peach (Tatsuki et al 2013), poplar ) and citrus (Xie et al 2015). Until now, no SAUR gene had been reported in P. edulis (PheSAUR).…”
mentioning
confidence: 99%